The Legality and Legitimacy of Marijuana Consumption in Nigeria (2016)
In recent times, marijuana has enjoyed a momentous rise in consumption despite the various campaigns for the abolition or complete eradication of the consumption of illicit drugs in Nigeria. In the bid to restrain or exterminate the consumption, there has been a rise in the application of penal sanctions on the farmers, the sellers and the consumers of marijuana in Nigeria.Employing a discursive analysis of secondary data, this paper, therefore, raises the question of whether the trend in the level of punishment has developed in harmony with popular opinion, something which both antagonists and supporters of penalties of greater severity seem to take for granted